Relationship between resilience, optimism, and burnout in Pan-American athletes - Tutte-Vallarino, Veronica; Malán-Ernst, Estefanía; Reyes-Bossio, Mario; Peinado-Portero, Ana; de Álvaro, Julio Imbernón; Ortín Montero, Francisco José; Garcés de Los Fayos Ruiz, Enrique J. (Frontiers in Psychology, 2022)
Aims A series of knowledge has been developed on burnout syndrome in the sports context that has allowed, since the origin of its study by Flippin (1981), to generate a solid theoretical structure that requires new contributions to delve into those aspects that have been less addressed, as is the case of optimism and resilience when it comes to linking them to the syndrome in top-performance athletes. For this purpose, the Burnout Inventory for Athletes (IBD-r), the Resilience Scale adapted to Spanish, and the Life Orientation Scale-Revised (LOT-R) for optimism were used. Methods From this perspective, the study was approached with 121 Uruguayan athletes who participated in the last Pan American Games, assuming practically all the subjects who have this level of sport (142) considering gender and type of sport. Results The results indicate that 67% of the sample presents burnout symptoms for the emotional exhaustion dimension, and moderate resilience and optimism. Although there are no significant differences attributable to gender or type of sport, this contribution allows us to continue focusing on future work and further analysis. The type of sport presented statistically significant differences in relation to the personal competence dimension and the type of sport. Conclusion Resilience and optimism obtained a clear influence on the occurrence of burnout, in a statistically negative sense, showing themselves as interesting prevention strategies for future lines of research, where it is essential to design interventions that teach emotional skills to manage adversity and prevent burnout.